What students need to know about good talk: Be BRAVE. Issue 3 (27th May 2017) - Rudnitsky, Al; Barclay, Catharine; Binger, Lauren
Abstract: This study explores the effectiveness of a workshop and accompanying conceptual framework designed to help middle school students become better participants in group work. The framework is designated BRAVE (build on ideas, risk tentative thoughts, ask good questions, value other perspectives, and use evidence). The framework is based on research identifying the features of effective group participation. The workshop, through a variety of experiences, introduces this framework to students. Two fifth- and two sixth-grade classes participated in the workshop. During the workshop, students articulate and record their ideas about group work. The article describes the workshop in detail. The article also examines evidence of learning that indicates students are able to meaningfully incorporate the BRAVE framework into their thinking about groups and group work.